Changes in Tear Proteome After Acupuncture Treatment in Dry Eye - Tong L (Dove Medical Press, 2021)
Louis Tong,1– 4 Lei Zhou,3– 5 Siew Kwan Koh,5 Yan Gao,5 Hla Myint Htoon,1,3 AiHua Hou,1,3 Lu Deng,6 Qi-Ping Wei,7 Pat Lim8 1Ocular Surface Research Group, Singapore Eye Research Institute, Singapore; 2Corneal and External Eye Disease Service, Singapore National Eye Centre, Singapore; 3Eye-Academic Clinical Program, Duke-National University of Singapore (NUS) Medical School, Singapore; 4Department of Ophthalmology, Yong Loo Lin School of Medicine, NUS, Singapore; 5Ocular Proteomics Platform, Singapore Eye Research Institute, Singapore; 6Department of Statistics and Applied Probability, Faculty of Science, NUS, Singapore; 7Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 8Singapore Chung Hwa Medical Institution, SingaporeCorrespondence: Louis TongSingapore National Eye Centre, 11, Third Hospital Avenue, 168751, SingaporeTel +65 9818 6221Fax +65 62252568Email Louis.tong.h.t@singhealth.com.sgLei ZhouSingapore Eye Research Institute, The Academia, 20 College Road, Level 6, 169856, SingaporeEmail zhou.lei@seri.com.sg